2012
DOI: 10.1017/s0033291712001936
|View full text |Cite
|
Sign up to set email alerts
|

Self-critical perfectionism and its relationship to fatigue and pain in the daily flow of life in patients with chronic fatigue syndrome

Abstract: This is the first study to show that SCP predicts both fatigue and pain symptoms in CFS in the daily course of life. Hence, therapeutic interventions aimed at targeting SCP should be considered in the treatment of CFS patients with such features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
(107 reference statements)
3
26
0
1
Order By: Relevance
“…In conclusion, the present study shows that pretreatment self‐critical perfectionism in chronic pain may negatively impact pain perception following a brief CBT‐based multidisciplinary intervention. This finding corroborates previous research highlighting the importance of self‐critical or maladaptive perfectionism in the maintenance of chronic pain and related conditions, and its negative impact on treatment outcome in brief, focused treatments …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, the present study shows that pretreatment self‐critical perfectionism in chronic pain may negatively impact pain perception following a brief CBT‐based multidisciplinary intervention. This finding corroborates previous research highlighting the importance of self‐critical or maladaptive perfectionism in the maintenance of chronic pain and related conditions, and its negative impact on treatment outcome in brief, focused treatments …”
Section: Discussionsupporting
confidence: 91%
“…Self‐critical perfectionism was measured with the self‐criticism subscale of the Depressive Experiences Questionnaire (DEQ) . The DEQ has shown good reliability and validity, also in patients with chronic pain and fatigue conditions . Pain intensity was assessed using the visual analog scale (VAS) of the McGill Pain Questionnaire—Short Form, ranging from no pain (0 mm) to the worst possible pain (100 mm).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Kempke et al showed a negative influence of self-critical perfectionism on fatigue and pain in CFS patients. 50 The main principle of GET is avoidance of physical deconditioning from prolonged rest and a gradual return to appropriate physical activities. 60 An exercise program is devised by a therapist to improve the patient's aerobic condition, using variations of exercise therapy such as cycling, walking, and swimming in mixed levels of intensity.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Finally, not only research on patient (sub)groups, but also longitudinal N=1 studies using ecological momentary assessment (see e.g., [25] and [31]) may substantially contribute to a better insight into how these patients' loss of adaptability can be restored.…”
Section: Customizing Treatmentmentioning
confidence: 99%
“…As a recent illustration of this research, maladaptive perfectionism has been shown to predict the patient's daily level of fatigue and pain, supporting the hypothesis that this personality trait may play a role in the course of CFS/FM. [31] Biopsychosocial illness mechanisms It is highly probable that symptoms and functional limitations of CFS/FM-patients are based on a complex interplay of psychosocial factors and pathophysiological dysfunctions.…”
Section: Introductionmentioning
confidence: 99%